92 Primary care prescriptions for statins in england 1998–2015. (5th June 2017) - Raza, Sadaf; Patel, Ketna; Patel, Hitesh; Primus, Christopher; Tyebally, Sara; Bhattacharyya, Sanjeev; Hayward, Carl
Abstract : Introduction: Statins are widely prescribed for the prevention of cardiovascular events. A change in 2014 of the National Institute for Health and Care Excellence (NICE) guidelines for the primary prevention of cardiovascular events, lowered the threshold for prescribing statins from a 10 year risk of cardiovascular events of 20% to 10%. It was anticipated that this would result in over 4 million new patients commencing a statin. We sought to determine the trends in statin prescriptions in primary care in England over a 17 year period. We also analysed data from the Quality and Outcomes Framework (QOF) in 2015/16 to assess QOF achievement for prescription of statins for primary prevention. Methods: We conducted a nationwide retrospective study. Data were obtained from the Prescription Cost Analysis system, which holds information on every prescription dispensed in the community in England, covering a population of over 50 million people. We obtained data for four statins from 1998 to 2015. We analysed data collected from the Quality and Outcomes Framework, an incentive programme rewarding primary care for achieving targets. We reviewed the outcomes of care commissioning groups (CCGs) for the QOF indicator CVDPP001 defined as: for primary prevention in patients with hypertension and a cardiovascular risk assessment score 20%, the proportion treated with a statin. Results: The total number of statins prescribed has increased annually from 1998 (4.5 million prescriptions) to 2015 (66.3 million prescriptions) in a sigmoid pattern (Figure 1). There has not been a significant increase in statin prescriptions since the change in NICE guidelines in 2014. The majority of statin prescriptions are for simvastatin or atorvastatin. From 1998 to 2005 both were prescribed equally and more frequently on an annual basis. In 2005 prescriptions for atorvastatin fell, then plateaued, while prescriptions for simvastatin increased. In 2012 prescriptions for atorvastatin increased while simvastatin prescriptions fell. For QOF CVDPP001, out of 209 CCGs, 49 achieved 100% and the vast majority reached>95% (Figure 2). Conclusions: Our data demonstrate that the number of statin prescriptions has increased annually from 1998 to 2015. The 2014 NICE guidance has not resulted in a significant increase in statin prescriptions, in fact the rate of increase in prescriptions is beginning to plateau. The QOF for statin use in primary prevention has not yet adopted the new NICE guidelines and it may be that a change in prescribing trends is only seen after this occurs. The current QOF target is achieved to a high degree so it is likely that a new QOF with a 10% risk cut-off could also be met. The trends in prescribing of simvastatin and atorvastatin are likely cost driven, with an increase in simvastatin prescribing in 2004 and atorvastatin prescribing in 2012 correlating to the expiration of the UK patents for each drug.